Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41420-021-00768-7
|View full text |Cite
|
Sign up to set email alerts
|

Berberine alleviates liver fibrosis through inducing ferrous redox to activate ROS-mediated hepatic stellate cells ferroptosis

Abstract: Berberine (BBR) has been explored as a potential anti-liver fibrosis agent, but the underlying mechanisms are unknown. In the current study, we aimed to investigate the molecular mechanisms underlying the effect of BBR against liver fibrogenesis in thioacetamide (TAA) and carbon tetrachloride (CCl4) induced mouse liver fibrosis. In addition to i.p. injection with TAA or CCl4, mice in the treatment group received BBR intragastrically. Concurrently, combined with TAA and BBR treatment, mice in the inhibitor grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 61 publications
1
37
0
Order By: Relevance
“…Abnormal endoplasmic reticulum (ER) stress, oxidative stress, autophagy and ferroptosis, accompanied by inflammasome-associated signals, are common features of fibrogenesis. ( Koo et al, 2016 ; Kim et al, 2017 ; Yang et al, 2021 ; Yi et al, 2021 ; Zhang et al, 2021 ). However, the pathogenesis of HSC activation and liver fibrosis remains unclear.…”
Section: Mechanisms Of Hepatic Stellate Cells Activation and Liver Fi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormal endoplasmic reticulum (ER) stress, oxidative stress, autophagy and ferroptosis, accompanied by inflammasome-associated signals, are common features of fibrogenesis. ( Koo et al, 2016 ; Kim et al, 2017 ; Yang et al, 2021 ; Yi et al, 2021 ; Zhang et al, 2021 ). However, the pathogenesis of HSC activation and liver fibrosis remains unclear.…”
Section: Mechanisms Of Hepatic Stellate Cells Activation and Liver Fi...mentioning
confidence: 99%
“…In fibrotic mouse models, we found that BBR alleviates liver fibrosis by inducing ferrous-ion redox reactions to activate reactive oxygen species (ROS)-mediated ferroptosis in hepatic stellate cells, which suggests a possible strategy for the treatment of liver fibrosis. ( Yi et al, 2021 ). Similar effects of BBR in carbon tetrachloride (CCl 4 )-induced liver fibrosis models were also demonstrated by other team recently.…”
Section: Anti-fibrosis Effects Of Berberine In the Livermentioning
confidence: 99%
“…In addition, damaged autophagy potentiated BBRmediated ferritin hydrolysis, which increased cellular iron overload and triggered HSC iron death through the ubiquitin-proteasome pathway in HSC. Overall, BBR reduces LF through triggering ferrous redox to activate iron death in HSCs [218] .…”
Section: Berberinementioning
confidence: 97%
“…For one thing, phytochemicals could induce ferroptosis to suppress the progression of liver fibrosis and HCC. For instance, magnesium isoglycyrrhizinate, derivatives of artemisinin (such as artemether, artesunate, and dihydro-artemisinin (DHA)), wild bitter melon extracts, chrysophanol, and zalkaloid berberine could block the development of liver fibrosis by triggering HSC ferroptosis [ 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 ]. Besides, several studies revealed that DHA could trigger ferroptosis to block HCC growth by promoting PEBP1/15LO formation or an unfolded protein response [ 153 , 154 ].…”
Section: Cell Death In Liver Diseasesmentioning
confidence: 99%